Investigation of resonant polarisation radiation from relativistic electrons passing through a tilted conducting periodical target; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 173, iss. 1-2 : Radiation from Relativistic Electrons in Periodic Structures - Chefonov O. V.; Kalinin B. N.; Karataev P. V.; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Vnukov I. E.; Shibata Y. (2001, 2001)
Title screen